Jaringan Ulama Bogor : Pejuang Islam Sejak Era Utsmaniyyah (Abad 19 – 20 M) - Dhaiman, Arif Noor (PT. Student Rihlah Indonesia, 2025)
Bogor is a region of Tatar Sunda that has a long history. Known as Pakuan, which was the center of Pajajaran, it was liberated by the Sultanate of Banten during the reign of Maulana Yusuf ibn Hasanuddin ibn Sunan Gunung Jati Syarif Hidayatullah. The purpose of this study is to analyze the Bogor Ulama Network: Islamic Warriors since the Ottoman Era (19th-20th centuries AD). This research uses a historiographical approach with descriptive analysis, interviews, observation, and library research using books, journals, and other related literature. Based on the results of the study, the struggles of Habib Keramat Empang, Dalem Solawat, Syaikh Baing Yusuf, Syaikh Mukhtar 'Atharid, and Mama Abdullah ibn Nuh represent the Bogor Ulama Network of the 19th-20th centuries. Their influence was not limited to Bogor, but extended throughout the Sundanese and Javanese regions, Kelantan, Selangor, Penang, Johor, and even Mecca al-Mukarramah. Some served in education and da'wah, while others became village chiefs and regents. What is clear is that all of them were Islamic warriors from the era of the Ottoman Caliphate until the era after Indonesia's independence.